ANALISIS EMOSI SISWA YANG MENONTON FILM PORNO DI SMP NEGERI 3 PUJUD T.P.2013/2014 - Asyari, Abu Asyari Abu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
AbstractThis studyaims to determinethe level ofstudentemotionsthatwatching porninSMP Negeri 3Pujud2014, thebackground for theexistence ofthe phenomena seenin schools, namely: Problemstudyhowemotionspictureof studentswhowatch pornatSMP Negeri 3Pujud2014. The method usedinthisresearchisdescriptivemethod. Location of the studyare inSMP Negeri3Pujud. Subjects inthis study werestudents of classVI, VII, IXSMP Negeri3Pujudtakenwithsaturatedsampletechnique. Dataanddata collectiontoolwasa questionnaireformstudentemotionswatching porninSMP Negeri 3Pujudmadebythe researchers themselvesbased on thelatticewithalternativeanswersYES and NO. Data analysis techniqueusingbenchmarkcategoriesbased onthe normal curvein accordancewith the opinion ofthe JWPophamandSirotnikK.Ain, ArlizonR., (1998; 100) and thepercentageformula(Anas Sudijono, 2004:170). Conclusion Theresults ofthis study basedonthe results ofthe calculation ofbenchmarksemotionallevelstudentswhowatch pornatSMP Negeri 3Pujudin middle categoryin accordancewiththe results ofthe analysis. As a follow upofthis studycanresearchersrecommend thatthe partiestobe able topresumablyprovide an explanationandinputandadvicethat isuseful for learnersin order toavoid theeffects ofundesirable. Thesubsequent researchersto conductfurther researchin view ofthe present study onlyrefers tothose aspects thatstillneedfurtherimprovement. Keywords: EmotionStudentsWatchingPorn Movies